EFFECTIVENESS OF MARKETING IN THE COMPANY'S VALUE MANAGEMENT SYSTEM (Marketing Journal, 2025)
The article examines the issues of the influence of marketing activities on the formation of the efficiency of management of internal subsystems of economic entities: production, investment and innovation activities, personnel, finance, and resource manage ment. In addition, the article examines the economic efficiency of investments in marketing research - growth of net profit, net cash flow and value of company.
Keywords: marketing; value management system production management; investment management; financial management; human resources management; net profit; evaluation of marketing effectiveness; net cash flow; value of company